Level of Language Formality in ‘Perahu Kertas’ (2009) by Dee Lestari: A Translation Perspective - Jhovanny, Anggie; Suparto, Suparto (International Journal of English and Applied Linguistics (IJEAL), 2024)
As time progresses, variations or diversities in language are growing, either in terms of words, phrases, clauses or sentences. Something that is not missed from the spotlight is the difference in language procedures based on placement or situation. Diversity in language use can also be visible in any society life, such as in professional, education, business, or even daily interaction or conversation. This research is sociolinguistic research. One of the discussions in this research is the level of language formality. This research aims at analyzing the translation of the level of language formality. This research analyzes the translation of various forms of language formality from the 2009 Indonesian novel Perahu Kertas by Dee Lestari and the English version of Paper Boat (2017), which is translated by Tiffany Tsao. This research used the Language Formality theory by Joos (1967) from his book The Five Clocks: A Linguistic Excursion Into the Five Styles of English Usage. This research uses a qualitative descriptive method, using qualitative data (textual), which is described descriptively.  This research found that the novel used four types of levels of formality language, which are 57 data of casual style language, 43 data of consultative style language, 40 data of intimate style language, and seven data of formal style language. The frozen-style language has not been found